DEVELOPMENT OF METHOD FOR DETERMINING AND CORRECTING PARAMETERS OF THE WORKING ORBIT OF THE EARTH REMOTE SENSING SATELLITE - K V Mikhaylovskiy; M A Gorodetsky (RUDN Journal of Engineering Research, 2017)
A technique for the complex analysis of the characteristics of orbits used for space vehicles for remote sensing of the Earth (RSE), taking into account their trajectory, is proposed. The results of mathematical modeling of the operating conditions of such devices are presented. The technique is tested taking into account the input parameters of the orbit of the BelKA spacecraft. The technique will be useful in choosing of complex orbital characteristics for RSE spacecraft at the stage of technical proposals.